A study of 1000 galaxies with unusually young and massive stars in the SDSS: a search for hidden black holes. Issue 1 (9th April 2022) - Kauffmann, Guinevere; Maraston, Claudia; Comparat, Johan; Crowther, Paul
ABSTRACT: We select 1076 galaxies with extinction-corrected H α equivalent widths too large to be explained with a Kroupa initial mass function, and compare these with a control sample of galaxies that is matched in stellar mass, redshift, and 4000 Å break strength, but with normal H α equivalent widths. Our goal is to study how processes such as black hole growth and energetic feedback processes from massive stars differ between galaxies with extreme central H α emission and galaxies with normal young central stellar populations. The stellar mass distribution of H α excess galaxies is peaked at $3 × 10^{10}\, {\rm M}_{\odot }$ and almost all fall well within the star-forming locus in the [O iii ]/H β versus [N ii ]/H α Baldwin, Philipps & Terlevich diagram. H α excess galaxies are twice as likely to exhibit H α line asymmetries and 1.55 times more likely to be detected at 1 GHz in the VLA FIRST survey compared to control sample galaxies. The radio luminosity per unit stellar mass decreases with the stellar age of the system. Using stacked spectra, we demonstrate that [Ne v ] emission is not present in the very youngest of the radio-quiet H α excess galaxies with detectable Wolf–Rayet features, suggesting that black hole growth has not yet commenced in such systems. [Ne v ] emission is detected in H α excess galaxies with radio detections and the strength of the line correlates with the radio luminosity. This is the clearest indication for a population of black holes that may be forming in a subset of the H α excess population.